2022
DOI: 10.1177/01430343221107394
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and depressive symptoms among Australian female boarding school students

Abstract: Loneliness in adolescence is a risk factor for the development and maintenance of a myriad of mental health conditions, especially among females. Adolescent females in boarding schools spend prolonged periods away from family and may therefore be more prone to experiencing loneliness and depression. Research into this significant issue is limited, however. The present study compared the levels of loneliness and depressive symptoms of 403, 13–17 year old adolescent females from a range of boarding and non-board… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Analyses of questionnaire responses revealed that only two dimensions of homesickness were predictive of psychological distress: ruminating about home and loneliness. These homesickness dimensions have been previously reported as contributing to psychological distress in secondary (Rudrum et al, 2022) and college boarding students (Moeller & Seehuus, 2019;Morrison & O'Connor, 2005). As protective measures, boarding students participating in the focus groups identified social interaction, immersion in activities, routine and keeping busy as antidotes to homesickness.…”
Section: Overcoming Homesicknessmentioning
confidence: 81%
See 3 more Smart Citations
“…Analyses of questionnaire responses revealed that only two dimensions of homesickness were predictive of psychological distress: ruminating about home and loneliness. These homesickness dimensions have been previously reported as contributing to psychological distress in secondary (Rudrum et al, 2022) and college boarding students (Moeller & Seehuus, 2019;Morrison & O'Connor, 2005). As protective measures, boarding students participating in the focus groups identified social interaction, immersion in activities, routine and keeping busy as antidotes to homesickness.…”
Section: Overcoming Homesicknessmentioning
confidence: 81%
“…In particular, more information is needed regarding which aspects of sleep are most disrupted, for example, the timing of sleep versus the frequency and duration of nocturnal awakenings. A further issue is that secondary school boarding students typically report greater psychological distress than day-student peers (Fisher et al, 1984(Fisher et al, , 1990Lester & Mander, 2020;Rudrum et al, 2022;Wahab et al, 2013). Poor sleep is likely to play a contributing role but whether this is in addition to already well-established predictors of psychological distress such as gender (Campbell et al, 2021) and homesickness (Demetriou et al, 2021;Fisher et al, 1984Fisher et al, , 1990Stroebe et al, 2002;Thurber et al, 2007;Thurber & Walton, 2012) remains to be tested.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Foremost amongst these issues is being away from family and adaptation problems, which are important enough to be discussed at Turkish Grand National Assembly (TGNA) (Eraslan, 2006). When examining the international literature, it is observed that boarding schools are mostly for adolescents, and prominent issues include mental health (Aisyaroh and Ediyono, 2023;Hopkins et al, 2023), psychological resilience (Langham et al, 2018;Redman-MacLaren et al,2017), loneliness (Baru, et al, 2020;Rudrum, 2020), and adaptation (Sri-Wahyuni and Barus, 2020;Su et al, 2019). Hence, there is a need for effective psychological guidance and counseling services to support the psychological and social development of the students at RBSs and help them with their emotional problems (Atli, 2018;Pavletic et al, 2016).…”
mentioning
confidence: 99%